Adecuación y puesta en funcionamiento de un equipo de transmisión de televisión analógico. - Orellana González, Geovanny Eduardo (2009)
The technical formless present consists on the "ADAPTATION AND SETTING IN OPERATION OF AN ANALOGICAL TRANSMITTER OF TELEVISION", the practical work of grade will not be part of the shop of electronic of the Area of Energy, the Industries and the Natural Resources Renewable of the UNL, which consists of the following elements and teams: Wooden modeled piece of furniture for the location of the teams of the project, a transmitter of General television Electric of 300 mW of power, camera of video Olympus, coaxial cable RG-6, a splitter of an entrance and two exits, two balunes of 75 at 300Ω, 10 connectors BNC, two antennas of high gain. Also in the document is the design, construction and radiation of the the transmission antennas, modulation types, compound video signs.